2019
DOI: 10.1093/mnras/stz518
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the Tucana Dwarf Galaxy: an unusually dense dwarf in the Local Group

Abstract: We present new FLAMES+GIRAFFE spectroscopy of 36 member stars in the isolated Local Group dwarf spheroidal galaxy Tucana. We measure a systemic velocity for the system of v Tuc = 216.7 +2.9 −2.8 kms −1 , and a velocity dispersion of σ v,Tuc = 14.4 +2.8 −2.3 kms −1 . We also detect a rotation gradient of dv r dχ = 7.6 +4.2 −4.3 kms −1 kpc −1 , which reduces the systemic velocity to v Tuc = 215.2 +2.8 −2.7 kms −1 and the velocity dispersion to σ v,Tuc = 13.3 +2.7 −2.3 kms −1 . We perform Jeans modelling of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…The velocity anisotropy was well-recovered in all cases, except PlumCoreOm for which 1,000 tracers was insufficient to detect the radial anisotropy at large radii (Read et al 2021). In Gregory et al (2019), G S was tested on mock data for fewer tracers (20, 100 and 500 tracer stars). There, a similar bias towards low densities at large radii was reported.…”
Section: Data Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The velocity anisotropy was well-recovered in all cases, except PlumCoreOm for which 1,000 tracers was insufficient to detect the radial anisotropy at large radii (Read et al 2021). In Gregory et al (2019), G S was tested on mock data for fewer tracers (20, 100 and 500 tracer stars). There, a similar bias towards low densities at large radii was reported.…”
Section: Data Availabilitymentioning
confidence: 99%
“…However, the code has a tendency to underestimate the density at large radii 𝑅 2𝑅 1/2 (Read et al , 2021. Furthermore, for small numbers of stars, or where the measurement error on each star is large, the binning method within the code can become biased (Gregory et al 2019;Zoutendijk et al 2021).…”
Section: Mass Modelling With G Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although difficult to detect, these ultra-diffuse systems have the potential of yielding important clues to our understanding of dwarf galaxy formation. Indeed, the kinematics of their stars have proved challenging to interpret: some have extremely low velocity dispersion, hinting at very low dark matter densities (e.g., Crater II, And XIX, Collins et al 2013;Caldwell et al 2017), while others inhabit surprisingly dense haloes, according to the kinematical evidence (e.g., Draco, Tucana, Walker et al 2007;Gregory et al 2019). These diverse properties are mirrored by other UDGs outside the Local Group (LG), where some have been associated with massive dark haloes (van Dokkum et al 2016;Beasley et al 2016), whereas others have been found to contain little obvious evidence for dark matter (van Dokkum et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Of the other SIDM models, vd100 model predicts the fewest subhaloes, with 90 per cent of CDM at 𝑀 sub ∼ 10 8 M and 75 per cent at 𝑀 sub ∼ 10 7 M . This demonstrates part of the way in which the vdSIDM model addresses the TBTF problem by predicting fewer subhaloes capable of hosting luminous galaxies, with the aforementioned mass range being synonymous with the dark matter halo mass of 'problematic' dwarf galaxies such as Tucana (Gregory et al 2019).…”
Section: The Subhalo Populationmentioning
confidence: 95%